2006
DOI: 10.1510/icvts.2005.113837
|View full text |Cite
|
Sign up to set email alerts
|

Assessing clinical performance in cardiac surgery. Does a specialised clinical database make a difference?

Abstract: We compared mortality rates league tables for six cardiac surgery centres developed using an administrative database (integrated with information on patients' EuroSCORE) with those drawn from a specialised clinical database. Data from 4017 patients undergoing cardiac surgery over the period January 1st-December 31st 2003, and identified both databases were used. Case mix adjusted in-hospital mortality rates were estimated relying on information provided by each database, and league tables were drawn from both.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…However, we did not find relevant changes in recording of co-morbidities in our study population over the years (data not shown). In agreement with previous reports, the prevalence of certain co-morbidities and risk factors was relatively low in our study population, indicating underreporting of co-morbidities and detailed clinical information in the administrative database [65]. However, underreporting was non-differential in the years included in our analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we did not find relevant changes in recording of co-morbidities in our study population over the years (data not shown). In agreement with previous reports, the prevalence of certain co-morbidities and risk factors was relatively low in our study population, indicating underreporting of co-morbidities and detailed clinical information in the administrative database [65]. However, underreporting was non-differential in the years included in our analysis.…”
Section: Discussionsupporting
confidence: 91%
“…However, underreporting was non-differential in the years included in our analysis. Moreover, a previous Italian study [65] assessing clinical performance in cardiac surgery demonstrated that the use of an administrative database provided similar league tables as a more complex specialized database.…”
Section: Discussionmentioning
confidence: 99%
“…The Emilia-Romagna Regional Registry of AAAD includes patients from different cardiothoracic regional centres as previously described [10]. Differences in patient management and operative In 154 patients (30.7%), the aortic repair was performed without circulatory arrest.…”
Section: Operative Techniquementioning
confidence: 99%
“…The prevalence of certain comorbidities was relatively low in our study population, indicating underreporting in the administrative database (Fortuna et al. ). However, underreporting was non‐differential in the years and regions included in our analysis.…”
Section: Discussionmentioning
confidence: 55%
“…A previous Italian study (Fortuna et al. ) demonstrated that an administrative database provided similar league tables as a more complex specialized database. Regarding the increase in timely PCI, we cannot exclude a “risk‐avoidance creep,” with hospitals selecting lower risk patients and avoiding higher risk ones.…”
Section: Discussionmentioning
confidence: 99%